The comparison of bio electrical properties of leech oil and aroma oil for foot refloxology massage / Fawad Ahmed Memon - Fawad, Ahmed Memon (2012)
Massage is one of the techniques for relaxing muscle and to reduce pain. It is use for maintaining condition of body or treats human diseases for thousands of years. Foot massage basically is a massage treatment around calf muscle until underneath foot area where it initiates stimulation to anatomical organs. In this thesis, the bioimpedance parameters (BI) of people undergoing reflexology therapy are analyzed. A comparison between bioimpedance (BI) parameters of a subject using aroma cream and leech oil is studied. The measurement of bioimpedance parameters is done by using Bodystat Quadscan 4000. The main purpose of this study is to investigate the effect of reflexology in term of resistance (R); reactance (X); impedance (Z); Phase angle; and capacitance (C) of male and female subjects that can be measured as bioimpedance (BI) parameters. All these parameters analyzes by using statistical analysis program called SPSS. The result showed that there is significant different between the mean of each bioimpedance parameters of massage using aroma and massage using leech oil. The mean of all bioimpedance parameters for massage using leech oil is significantly higher than the mean of the bioimpedance parameters for the massage using aroma cream. It is concluding that leech oil give more beneficial effect to the calf muscle